(untitled) (Research, Society and Development, 2022)
Evidence of impact of dietary factors on development of coronary artery calcification remains uncertain. The objective of the study was to evaluate the association between the intake carbohydrates, proteins, total fats, saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA), trans fatty acids (TFA) cholesterol and fiber with cardiovascular risk. Cross-sectional analysis from 181 dyslipidemic patients. The Coronary Calcium Score (CCS) was used to measure cardiovascular risk. 24-hour recalls were applied and the Multiple Source Method was used to adjust dietary variability. The mean values of the cardiovascular risk categories were compared by analysis of variance, using ANOVA and Kruskal-Wallis. Tukey’s post-test was used for multiple analyzes. Simple and multiple binary logistic regression, was used as a measure of association between nutrient intake and cardiovascular risk. Age, male gender, comorbidities and drug treatment were significantly prevalent in those with CCS>100. The average total energy intake was 1315.6 kcal. Total energy and macronutrient intake were higher among men (p < 0.05). No significant results were found regarding the association between cardiovascular risk and macronutrient intake. Fiber intake was inversely associated with cardiovascular risk, regardless of confusion factors (OR:0.918; 95% CI:0.845-0.999; p=0.047). The resultes that there was no association between nutrientes analyzed to cardiovascular risk assessed by CCS. However, the increase of dietary fiber intake in 1 g/day has been shown to reduce the of future cardiovascular events in 8.2% among individuals in the highest risk category. Therefore, we strongly recommend that fiber intake be encouraged.